ON COLOURING MAPS & SEMIDIRECT PRODUCT GROUPOIDS ON GROUP-POSETS - ABDUL AALI J. MOHAMMAD (College of Education for Pure Sciences, 2007)
Abstract In this paper we will study the (G,H)- posets , to give a condition of freeness on colouring maps . Also we will look at the group - posets from the view point of the category theory . That is to give some results on semi-direct product poset groupoid.